1959
DOI: 10.1111/j.1151-2916.1959.tb12971.x
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric and Dielectric Properties of Ceramics in the System Potassium—Sodium Niobate

Abstract: From this it can be seen that in forming either the 3 : 5 or 2: 1 structures from the molten state or the oxides, the aluminum must decrease its coordination. On the other hand, the coordination of this ion in YAIOJ is the same or greater than in the oxides or in the molten state. As a result, YAlOa is readily formed from these starting materials even though it is a metastable compound under equilibrium conditions. The aluminum oxygen octahedra are, of course, the most important structural element of these str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
603
3
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,068 publications
(647 citation statements)
references
References 5 publications
34
603
3
7
Order By: Relevance
“…The dielectric constant and dielectric losses are shown in Fig. 7, the T O-T and T C are clearly observed, the T O-T is close to 200°C as reported in several works (Du et al, 2006;Egerton & Dillon, 1959). The Curie temperature also agrees well with that reported previously which is near to 420°C (Ringgaard & Wurlitzer, 2005;Singh et al, 2001).…”
Section: Piezoelectric Dielectric and Ferroelectric Properties Of Knnsupporting
confidence: 88%
See 2 more Smart Citations
“…The dielectric constant and dielectric losses are shown in Fig. 7, the T O-T and T C are clearly observed, the T O-T is close to 200°C as reported in several works (Du et al, 2006;Egerton & Dillon, 1959). The Curie temperature also agrees well with that reported previously which is near to 420°C (Ringgaard & Wurlitzer, 2005;Singh et al, 2001).…”
Section: Piezoelectric Dielectric and Ferroelectric Properties Of Knnsupporting
confidence: 88%
“…The conventional method is well-known and extensively used, and was the first method reported for the synthesis of KNN (Egerton & Dillon, 1959;Jaeger & Egerton, 1962;Shirane et al, 1954), since it is simple and low cost. Basically, it consists of mixing carbonates and oxide powders of the desired elements.…”
Section: Conventional Ceramic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was established that Ta substitution for Nb, changes the properties of KNbO 3 and the authors also demonstrated that small amounts of Ta for Nb could enhance the piezoelectric properties of KNN ceramics [72,91]. Saito et al [92] also developed a lead-free system containing a blend of alkaline niobate (T c = 415°C) based solid solution with LiTaO 3 (T c = 615°C).…”
Section: Knbo 3 -Based Ceramicsmentioning
confidence: 99%
“…It is a solid solution of ferroelectric KNbO 3 and antiferroelectric NaNbO 3 , exhibiting very high Curie temperature (T c = 420°C), good ferroelectric properties (P r = 33 lC/cm 2 ), and large electromechanical coupling (1-3x)NBT-2xKBT-xBt factors [72]. The phase diagram for the KNN system is shown in Fig.…”
Section: Knbo 3 -Based Ceramicsmentioning
confidence: 99%